2007
DOI: 10.30638/eemj.2007.035
|View full text |Cite
|
Sign up to set email alerts
|

Current Practice of Solid Waste Management in Malaysia and Its Disposal

Abstract: Malaysia is a country that has recorded a phenomenal economic development success story. One of the most important problems is solid waste due to inadequate management practices. This resulted in an increase in the amount of waste generated. The national average in at 0.5-0.8 kg/person/day, but in the cities the figures have escalated to 1.7 kg/person/day. This paper addresses the current practice of solid waste management and its disposal in Malaysia. Currently, the waste management approach being employed is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 7 publications
1
12
0
Order By: Relevance
“…As illustrated in Figure (3), almost 99% of the respondents stated that the containers are regularly emptied. This result is in line with one stand in the literature [20].…”
Section: Residents' Opinion Regarding Emptying Of Containers In Theirsupporting
confidence: 93%
See 1 more Smart Citation
“…As illustrated in Figure (3), almost 99% of the respondents stated that the containers are regularly emptied. This result is in line with one stand in the literature [20].…”
Section: Residents' Opinion Regarding Emptying Of Containers In Theirsupporting
confidence: 93%
“…Meanwhile, it is similar to the average generating rate in of the majority of Arabic cities, which is roughly calculated to be around (1.04 kg per person per day) [16]. However, in comparison, the range of generation rate in Al Marj city was higher than the per capita solid waste generation rate in Tehran in 2005 which was 0.88 kg per person per day [17] and was 0.86 kg per person in Santiago de Cuba, and lower than the per capita solid waste generation rate in China which was 1.21 kg per person per day [18] and almost similar to 1 kg per person day in Gümüşhane in Turkey [19] and also similar to 1 kg per person day in Penang, Malaysia [20]. Generation has been influenced by the time and seasons of the year, local culture, traditions and personal income.…”
Section: Introductionmentioning
confidence: 67%
“…By 2015, the amount is expected to be around 14 268 tons/day. This is equivalent to an increase of 0.5–0.8 to 1.7 kg per person and day 28.…”
Section: Introductionmentioning
confidence: 99%
“…This leaves the small-scale waste operators to not have the adequate initial capital to construct and improve their existing landfill facilities for LFG applications. Furthermore, the increase in land price poses a significant impact to the government and private companies in opening new sites for landfilling [41,42]. • Johari et al [33] reported that in Malaysia, 44.4% and 55.6% of methane emissions are from sanitary landfills and dumpsites, respectively.…”
Section: Lack Of Financial Support To Construct Sanitary Landfillsmentioning
confidence: 99%